Big Five personality traits and entrepreneurial financing decisions among Malaysian university students - Ying Lim, Ying; Siew Cheng, Mary Lee (International Journal of Evaluation and Research in Education (IJERE), 2025)
Psychological factors are increasingly recognized as crucial in shaping entrepreneurial behavior and outcomes. However, the uncertainty and ambiguity in the entrepreneurial landscape reveal a significant gap in our understanding of these influences. Examining how personality traits affect entrepreneurs’ ability to identify opportunities and secure funding is essential. More research is needed to explore the connections between personality, thought processes, and emotions in entrepreneurial finance. This study investigates the relationships between Big Five personality traits and entrepreneurial financing decisions (EFD), focusing on the mediating role of alertness and the moderating role of passion. Using a cross-sectional design, data from 485 Malaysian university students aspiring to become entrepreneurs were analyzed via structural equation modeling (SEM) in SmartPLS. The findings indicate that traits like agreeableness, extraversion, and openness to experience enhance entrepreneurial alertness, influencing financing decisions. Additionally, higher levels of agreeableness and extraversion promote greater alertness regarding financing. Passion significantly amplifies the positive effects of alertness on financing decisions. However, conscientiousness and neuroticism do not directly or indirectly affect alertness. The study emphasizes the need for policymakers to enhance entrepreneurship education by integrating personality development and opportunity recognition training while balancing financial metrics with qualitative factors like passion and alertness.